Validity and Reliably Test: An Analysis of Students’ Comprehension and Skill in Applied Physics - Angglena, Melly; Pandey, Fhandy (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The low level of students’nderstanding of basic physics concepts impacts their learning outcomes. To address this issue, several teaching methods were implemented, including project-based learning (PBL), problem-solving, simulation, interactive discussions, and group presentations. This study aims to enhance students understanding of the Applied Physics course in the Electrical System Engineering for Oil and Gas Program at Ambon State Polytechnic. This research employs a quantitative descriptive approach, with data collected through questionnaires from 25 first-semester students. The findings indicate that the applied methods positively contributed to improving students understanding, with 48% of students achieving a good level of comprehension and 24% reaching an excellent level. Factors supporting this improvement include students active engagement in the learning process, the use of technology in simulations, and more interactive and contextual teaching methods. Thus, the implementation of these innovative teaching methods has proven effective in enhancing students comprehension of Applied Physics concepts. Continuous evaluation and development of teaching strategies are necessary to ensure the ongoing improvement of learning quality in the future.